Circulating PD‐1 (+) cells may participate in immune evasion in peripheral T‐cell lymphoma and chidamide enhance antitumor activity of PD‐1 (+) cells - Wei Zhang; Haorui Shen; Yan Zhang; Wei Wang; Shaoxuan Hu; Dongmei Zou; Daobin Zhou (Cancer Medicine, 2019)
Abstract Peripheral T‐cell lymphoma (PTCL) is a heterogeneous disease with poor outcomes. We intend to explore the role of circulating PD‐1 (+) cells in tumor immune evasion in PTCL patients and the mechanism of chidamide as a regulator of immune‐associated medicine on PD‐1 (+) cells. Gene expression profiling (GEP) was performed on circulating PD‐1 (+) cells from 22 PTCL patients and 13 healthy subjects, and circulating PD‐1 (−) cells from 2 PTCL patients. PD‐1 (+) cells were treated with chidamide, and the production IFN‐γ and cytotoxicity were analyzed. GEP were performed on circulating PD‐1 (+) cells from 2 PTCL patients treated with chidamide combined with chemotherapy and 1 patient treated with traditional chemotherapy. GEP showed that genes associated with innate immune response were abnormally expressed in PD‐1 (+) cells of PTCL patients compared with healthy subjects, meanwhile the expression of CTLA‐4 was significantly higher in PD‐1 (+) cells than that of PD‐1 (−) cells. In vitro study revealed decreased level of IFN‐γ secretion and impaired cytotoxic activity of PD‐1 (+) cells compared with PD‐1 (−) cells, while chidamide could recover the deficiencies and upregulate adaptive immune‐associated genes in PD‐1 (+) cells of PTCL patients. Our research indicated that PD‐1 (+) cells might have deficiencies in innate and adaptive immune response and chidamide may reverse the defects.